A prospective study to compare the efficacy of noradrenaline verses terlipressin in hepatorenal syndrome in patients with advanced cirrhosis - Nayyar, Srishti; Kaur, Ranjeet; Mohan, Gurinder; Chandey, Manish (International Journal of Advances in Medicine, 2021)
Background: Hepatorenal syndrome (HRS) is functional renal failure occurring in advanced stage liver disease associated with poor prognosis. The best treatment is liver transplantation. Terlipressin is effective in treatment of HRS but noradrenaline has been suggested as cheaper and readily available alternative and we aimed to compare the efficacy of noradrenaline and terlipressin in patients with HRS. Methods: 30 patients were allocated to each group and group A received infusion of noradrenaline at dose of 0.5 mg/hr (maximum 3 mg/hr) and group B received terlipressin at dose 1 mg intravenously 6 hourly until reversal of HRS or completion of 7 days of therapy. Intravenous albumin (20 g/day) was given to both groups. Decrease in serum creatinine and increase in daily urine output and mean arterial pressure (MAP) helped us in comparison. Results: Out of 60 cirrhotics screened, 51 were randomised into group A (N=22) or group B (N=29). Baseline characteristics of both groups were similar. In group A, 0% showed complete response while 31.8% showed partial response but majority (68.2%) showed no response. In group B, 89.7% showed complete response and 6.9% showed partial response. Decrease in serum creatinine in both groups (group A- 3.91±1.58 mg/dl to 3.07±1.68 mg/dl; group B- 3.21±1.24 mg/dl to 1.36±0.87 mg/dl). Both groups showed an increase in MAP (group A- 76.93±6.18 mmHg to 89.49±6.93 mmHg; group B- 75.54±5.51 mmHg to 89.92±5.07 mmHg). Conclusions: Noradrenaline was not as effective as terlipressin in treatment of HRS.